Akhlak Sebagai Perisai Di Tengah Perubahan Gaya Hidup Modern - Suaidi Suaidi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to determine the function of morality as a light and guide of human life in an era that tends to change morals is very visible. Morals or manners have an important role in building a nation. The morals in question are akhlakul karimah or commendable morals. Someone who has good morals, then all his actions and behavior are good. In this way, a harmonious and peaceful life will be realized. One of the hadiths of the Prophet Muhammad, Saw, explained